The Effect of Chamfer Angle Variations on the Quality of Friction Welding Results of AZ-31B Magnesium - Ferdouza, Nouval; Risano, Ahmad Y E; Riszal, Akhmad; Tarkono, Tarkono (Journal of Engineering and Scientific Research, 2024)
Friction welding is one of the solid-state welding types. Friction welding is a joining process whose application melts the material itself by using the heat generated between the surfaces through a combination of rotational motion and the application of compressive loads. The use of magnesium alloys is widely used in various industrial fields, examples of magnesium alloy applications include coating materials from iron and steel as a means of protecting against corrosion. The use of AZ-31B series magnesium alloys has a high specific strength compared to other series such as AM. The purpose of this final project research is to determine the effect of the addition of chamfer angle on the tensile strength value and microstructure of AZ-31B magnesium friction welding results. From this research, the results obtained in tensile testing are that the addition of the chamfer angle to the surface of the weld specimen will increase the tensile strength value. The highest maximum stress value was obtained in the chamfer angle variation of 300 with an average of 228.525 MPa and the lowest maximum stress value was in the material that did not use the chamfer angle variation with an average of 105.722 MPa. Based on microstructure testing, it shows differences in ?- Mg and ?-Mg phase grains17 Al12 in each region, this is influenced by heat and also the melting generated from welding so that it changes its microstructure.